ISOLATION AND IDENTIFICATION OF FUNGI ASSOCIATED WITH SOILS AND DISEASED TOMATO PLANTS ON FARMERS’ FIELDS IN BENUE STATE NIGERIA (FUDMA JOURNAL OF SCIENCES, 2023)
A study was carried out to isolate and identify fungi associated with infected tomato plants and soils collected from tomato fields in major tomato growing Local Government Areas (LGAs) of Benue State, Nigeria. Fungi isolated from diseased tomato plant tissues and rhizospheric soils using the direct plate and soil dilution techniques respectively were identified through examination of cultural and microscopic features, aided by relevant identification keys and manuals. A total of 46 fungi belonging to 5 divisions and 14 genera were isolated from sampled plant and soil materials. Soil samples gave the highest number of fungal isolates, 31/46(67.39%) compared to plant materials, 15/46(32.61%). Plant and soil samples collected from Buruku LGA yielded the highest number of fungal isolates, 16 followed by Ushongo, 14, Gboko, 10, and lastly Tarka, 06. Fungi belonging to the Division Deuteromycota were the most frequently occurring, 76.09%, followed by Ascomycota, 13.04% and both Oomycota and Basidiomycota with 4.35% respectively. Members of the Zygomycota were the least occurring in the sampled materials with 2.17%. Fungi belonging to the genus Aspergillus were the most frequently occurring with 19.57%. The least frequently occurring fungi were those belonging to the genera Colletotrichum, Scopulariopsis, and Mucor, all having 2.17% frequencies of occurrence respectively. The study revealed the occurrence of fungi in tissues and rhizosphere of the tomato plant, which included several fungi genera of agricultural importance.
Keywords: Fungi, Identification, Infected Soils, Isolation, Tomato Plants